Garanties de l’autonomie patrimoniale des jeunes Églises en République démocratique du Congo - Mole-Mogolo, Gratien (L' année canonique, 2008)
A number of factors are an obstacle to the autonomous patrimony (protection of Church’s temporal goods) of the young Churches in the Democratic Republic of the Congo. They were brought to attention, amongst others, by Cardinal Malula. Propositions that concern the growth of this autonomy have been made by the pope John Paul II and by different african supra-episcopal assemblies. From a canonical point of view, institutional solutions and the inculturation of law with the creation of a particular law may equally contribute to a solution.